Introduction to Writing Citations and Reference Lists Using APA Style 7th Edition for Publishing in SINTA-Accredited National Journals - Rafiek, Muhammad (Universitas Lambung Mangkurat, 2025)
The introduction of reference writing and reference lists in the APA style 7th edition was motivated by changes in the rules for writing reference lists in scientific papers. The change from the rules for writing APA style 6th edition to APA style 7th edition requires the speed of S2 students in updating their information about APA style 7th edition. Students must also update their knowledge by writing references and reference lists in APA style 7th edition. Introduction to reference writing and reference list APA style 7th edition is very necessary, especially in writing a reference list of thesis reports and writing scientific articles. This introduction aims to enable 20 S2 students of the Indonesian Language and Literature Education Postgraduate Program of Universitas Lambung Mangkurat (ULM) for 2023/2024 to write a list of references according to the APA style 7th edition rules. This service method uses Service Learning (SL) in the form of an online introduction with Google Meet. The participants of this introduction amounted to 20 S2 students of the Indonesian Language and Literature Education Postgraduate Program of ULM for the academic year 2023/2024. The implementation technique is carried out by delivering material, providing direct examples, and observing the direct practice of participants in Google Meet impressions. This introduction activity will be held on Saturday, February 3, 2024, through Google Meet. The result of the introduction was that 20 participants successfully mastered writing references and reference lists in APA style 7th edition. This service concludes that 20 S2 students of the Indonesian Language and Literature Education Postgraduate Program of ULM for 2023/2024 can understand and apply reference writing and reference lists in APA style 7th edition.